2011
DOI: 10.4049/jimmunol.1001960
|View full text |Cite
|
Sign up to set email alerts
|

T Cell-Intrinsic Factors Contribute to the Differential Ability of CD8+ T Cells To Rapidly Secrete IFN-γ in the Absence of Antigen

Abstract: A subset of CD44hiCD8+ T cells isolated from C57BL/6/J (B6) mice, but not BALB/c/By/J (BALB/c) mice, rapidly secrete IFN-γ within 16 h of infection with Listeria monocytogenes. This Ag-independent response requires the presence of both IL-12 and IL-18. Previous studies showed that dendritic cells from B6 mice produced more Th1-type cytokines such as IL-12 than did those from BALB/c mice in response to L. monocytogenes infection. In this report, we demonstrate that the microenvironment in L. monocytogenes-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Cytokine responsiveness could also be modified: interestingly, the gene coding for IL-18bp, an inhibitor of IL-18 signaling, is induced by IL-4 in memory CD8 T cells. Recently, BALB/c memory-phenotype CD8 T cells have been shown to produce lower levels of IFN-g compared with C57BL/6 mice in response to a combination of IL-12/ IL-18 (45). This reduced responsiveness of BALB/c memoryphenotype CD8 T cells could result from an increased IL-18bp expression in response to the higher basal levels of IL-4 observed in these mice.…”
Section: Discussionmentioning
confidence: 91%
“…Cytokine responsiveness could also be modified: interestingly, the gene coding for IL-18bp, an inhibitor of IL-18 signaling, is induced by IL-4 in memory CD8 T cells. Recently, BALB/c memory-phenotype CD8 T cells have been shown to produce lower levels of IFN-g compared with C57BL/6 mice in response to a combination of IL-12/ IL-18 (45). This reduced responsiveness of BALB/c memoryphenotype CD8 T cells could result from an increased IL-18bp expression in response to the higher basal levels of IL-4 observed in these mice.…”
Section: Discussionmentioning
confidence: 91%
“…In vivo , the cells displayed surface and intracellular markers that are characteristic of naïvety (Figure 4, Figure 5), and they failed to produce IFNγ following peptide stimulation ex vivo (Figure 2). Nevertheless, we considered the possibility that the responding cells might not be truly naïve, and instead might be “virtual memory” cells, as described by others (33, 34). To address this concern, we repeated the above analyses with MACS-sorted P14 cells; a summary of the data is presented in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to antigen-induced true memory cells, however, IL-4-stimulated memory CD8+ T cells showed decreased expression of NKG2D and CCL5 with less cytolytic activity (Ventre et al, 2012). Also BALB/c CD8+ T cells respond poorly to IL-12 and IL-18 stimulation to produce IFN-γ compare to those of B6 mice, which was attributed to decreased induction of IL-12 and IL-18 receptors (Bou Ghanem, Nelson, & D’Orazio, 2011). Based on these observations, it has been suggested that IL-4 memory CD8 + T cells have functional superiority over antigen inexperienced naïve CD8+ T cells, but that IL-4-induced memory CD8+ T cells are less effective against pathogens compared to antigen-induced true memory cells (Ventre et al, 2012).…”
Section: The Role Of Innate Memory T Cells In Immunitymentioning
confidence: 99%